Mortality in vegetarians and comparable nonvegetarians in the United Kingdom. - Appleby, P; Crowe, F; Bradbury, K; Travis, R; Key, T (American Society for Nutrition, 2016)
Background Vegetarians and others who do not eat meat have been observed to have lower incidence rates than meat eaters of some chronic diseases, but it is unclear whether this translates into lower mortality. Objective The purpose of this study was to describe mortality in vegetarians and comparable nonvegetarians in a large United Kingdom cohort. Design The study involved a pooled analysis of data from 2 prospective studies that included 60,310 persons living in the United Kingdom, comprising 18,431 regular meat eaters (who ate meat ≥5 times/wk on average), 13,039 low (less-frequent) meat eaters, 8516 fish eaters (who ate fish but not meat), and 20,324 vegetarians (including 2228 vegans who did not eat any animal foods). Mortality by diet group for each of 18 common causes of death was estimated with the use of Cox proportional hazards models. Results There were 5294 deaths before age 90 in >1 million y of follow-up. There was no significant difference in overall (all-cause) mortality between the diet groups: HRs in low meat eaters, fish eaters, and vegetarians compared with regular meat eaters were 0.93 (95% CI: 0.86, 1.00), 0.96 (95% CI: 0.86, 1.06), and 1.02 (95% CI: 0.94, 1.10), respectively; P-heterogeneity of risks = 0.082. There were significant differences in risk compared with regular meat eaters for deaths from circulatory disease [higher in fish eaters (HR: 1.22; 95% CI: 1.02, 1.46)]; malignant cancer [lower in fish eaters (HR: 0.82; 95% CI: 0.70, 0.97)], including pancreatic cancer [lower in low meat eaters and vegetarians (HR: 0.55; 95% CI: 0.36, 0.86 and HR: 0.48; 95% CI: 0.28, 0.82, respectively)] and cancers of the lymphatic/hematopoietic tissue [lower in vegetarians (HR: 0.50; 95% CI: 0.32, 0.79)]; respiratory disease [lower in low meat eaters (HR: 0.70; 95% CI: 0.53, 0.92)]; and all other causes [lower in low meat eaters (HR: 0.74; 95% CI: 0.56, 0.99)]. Further djustment for body mass index left these associations largely unchanged. Conclusions United Kingdom–based vegetarians and comparable nonvegetarians have similar all-cause mortality. Differences found for specific causes of death merit further investigation.